Pendampingan Penyusunan Penelitian Tindakan Kelas bagi Guru PAUD di Kota Kupang Tahun 2023 - Tamelab, Maryance; Lanny Isabela Dwisyahri Koroh (Devotion: Jurnal Pengabdian Masyarakat, 2023)
Community engagement activities with Early Childhood Education (ECE) teachers in Kota Kupang are essential in improving the quality of education for children in their early developmental stages. This description outlines the various phases of the program, including socialization, workshops, group discussions, and assistance in developing Classroom Action Research (CAR). The outcomes of these activities include an improved understanding of CAR among ECE teachers, enhanced skills in CAR development, and support for publishing academic articles. Recommendations include the integration of digital technology, the provision of online guidance modules, and the establishment of continuous support mechanisms. By implementing these suggestions, the engagement activities can become more efficient and sustainable, contributing to the enhancement of early childhood education in Kota Kupang.